Secretome-Derived Cultured Cell System: Overview Towards Extracellular Protein Characterization and Biotechnological Applications - Anis Ben-Amar (Journal of Basic & Applied Sciences, 2021)
Secretome released by plant cells into the extracellular space, play crucial roles during development, embryonic potential acquisition, nutrient backing and stress acclimation. The dynamic nature of the extracellular proteome presents the challenge of identifying an array of extracellular proteins involved in the regulation of somatic embryogenesis in embryogenic suspension cultures. Extracellular proteins produced by cell cultures are perceived here as a central node of overlapping regulator factor network of totipotent somatic embryo developmental process. This paper reviews in a morphogenetic aspect the biological processes associated with extracellular protein-derived plant cultured cells and explores their prospective biotechnological applications in laboratories and biofactories retated to cell signaling and metabolism, developmental process, and biotic / abiotic stress tolerance. The role of extracellular proteins in acquisition and maintenance of embryonic potential and their relevance are especially emphasized.